Dispute Settlement Method at the Tribunal for Consumer Claims Malaysia: A Field Research: (Kaedah Penyelesaian Pertikaian di Tribunal Tuntutan Pengguna Malaysia: Satu Kajian Lapangan) (Kanun: Jurnal Undang-undang Malaysia, 2021)
The Malaysian government has enforced numerous consumer protection policies as a measure to provide consumers with the best consumer protection. This includes the establishment of the Tribunal for Consumer Claims Malaysia (TTPM), which was established under the Consumer Protection Act 1999. The aim was to ensure consumers receive the best protection of their rights. However, numerous issues have been highlighted, such as the TTPM's limited jurisdiction followed by inadequate understanding of consumers concerning the role and function of TTPM as a platform for remedial claims. Aiming to address the objectives of this research, the current study employed a qualitative approach to gather information by way of interview and observation. This study finds that the TTPM plays a very important role in providing a platform for remedial claims for consumers in Malaysia. The existence of the TTPM as a medium for consumer protection should be well-exploited as it benefits consumers. However, the roles and functions of the TTPM should be further developed. Thus, it is recommended that the relevant parties take steps to improve consumer protection rights in this country, in particular involving the TTPM.Keywords: Tribunal for Consumer Claims Malaysia, claim, remedy